Methyltransferase PRMT1 Is a Binding Partner of HBx and a Negative Regulator of Hepatitis B Virus Transcription - Benhenda, Shirine (American Society for Microbiology, 2013)
The hepatitis B virus X protein (HBx) is essential for virus replication and has been implicated in the development of liver cancer. HBx is recruited to viral and cellular promoters and activates transcription by interacting with transcription factors and coactivators. Here, we purified HBx-associated factors in nuclear extracts from HepG2 hepatoma cells and identified protein arginine methyltransferase 1 (PRMT1) as a novel HBx-interacting protein. We showed that PRMT1 overexpression reduced the transcription of hepatitis B virus (HBV), and this inhibition was dependent on the methyltransferase function of PRMT1. Conversely, depletion of PRMT1 correlated with increased HBV transcription. Using a quantitative chromatin immunoprecipitation assay, we found that PRMT1 is recruited to HBV DNA, suggesting a direct effect of PRMT1 on the regulation of HBV transcription. Finally, we showed that HBx expression inhibited PRMT1-mediated protein methylation. Downregulation of PRMT1 activity was further observed in HBV-replicating cells in an in vivo animal model. Altogether, our results support the notion that the binding of HBx to PRMT1 might benefit viral replication by relieving the inhibitory activity of PRMT1 on HBV transcription.